Study of attack in college volleyball - Yordan Portela Pozo; Elizabeth Rodríguez Stiven (Federación Extremeña de Balonmano; University of Extremadura, 2014)
Abstract This work is done in order to analyze the positive and negative aspects that affected the performance of the auction action in volleyball players performing this action (in this case male) in the Provincial University Games in 2012 in Havana , for which I take as a case study to the players of the University of Information Sciences and its opponents in those games, completing a total of 268 shares auctions in 7 games with a total of 15 September analyzed taking account of changes in the sport of Volleyball university in Cuba, data recorded by an observation sheet previously completed by the authors. The main results in this paper show that the greatest amount of shots that were done in these games were diagonal and a good percentage of positive linear auctions however were few and with very poor results. The primary role of the auction for the game's success is fully confirmed in this work because this action is achieved through many points in the game of volleyball and thus leads to a better result.